Maternal and child health nursing : care of the childbearing and childbearing family - Pillitteri, Adele (Philadelphia, Pennsylvania : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
This Study Guide to accompany the Seventh Edition of Maternal & Child Health Nursing, by Adele Pillitteri, is designed to help students practice and retain the knowledge from the textbook, and it is structured to integrate that knowledge and give students a basis for applying it in their nursing practice.
Unit 1: Maternal and child health nursing practice -- Unit 2: The nursing role in preparing families for childbearing and chidrearing -- Unit 3: The nursing role in caring for families during normal pregnancy, birth, the postpartum, and newborn period -- Unit 4: Thenursing role in caring fro a family during a complication of pregnancy, birth, or postpartal period -- Unit 5: The nursing role in helath promotion for a childrearing family -- Unit 6: The nursing role in supporting the health of ill children and their families -- Unit 7: The nursing role in restoring and maintaining the health of children and families with physiologic disorders -- Unit 8: The nursing role in restoring and maintaining the mental health of children and families
Includes bibliographical references and index.
Keywords: MATERNAL-CHILD NURSING